Combatting cultural nerve gas: maintaining traditional media and culture through local media production in Australia, Canada and Mexico. Issue 1 (1st April 2017) - Watson, Ian
In Australia in the 1980s, large numbers of remote Indigenous radio stations were established due to a perception that the introduction of mainstream satellite programming in remote areas would act as a form of cultural nerve gas (Remedio, 2012: 295) that would threaten the very isolation that had helped to preserve what remained of traditional language and culture (Guster, 2010: 9). There are parallels here with the development of remote media in Mexico and Canada, where local radio networks focusing on cultural content production were established in response to impending development and imposed sources of mass media. In each country, broadcasters in remote communities have, in recent years, been producing increasing amounts of hyper-local cultural and language-based content. This article examines the role played by Indigenous media in remote areas of Australia, Canada and Mexico in creating an alternative cultural voice for traditional communities and maintaining language and culture.